The conception of religious moderation in interfaith dialogue in Indonesia; Case study in Flores Nusa Tenggara Timur - Djainudin, Hamdhan (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2022)
This article discusses the concept of religious moderation in interfaith dialogue in Indonesia, especially in Flores, NTT. Religion, which in general is an ideology that is defensive and partial, at first glance does not appear in the Flores NTT community. This can be seen when commemorating religious holidays such as Eid al-Fitr or Christmas, where young people from different religious backgrounds help each other in the smooth implementation of the holiday, houses of worship that are often built side by side facilitate the process of interfaith interaction in Flores, NTT. This is an interest for the author to look further into the concept of religious moderation in Flores, NTT which can become an example in the application of religious moderation in Indonesia. Interpretive paradigm, an inductive qualitative approach, with qualitative multimethods, anthropology - ethnography to phenomenology, the author tries to map interfaith interaction patterns in the concept of religious moderation in NTT, where the result is, the position of religion as an ideology is replaced with the family, where the family is more exalted than religion, on the other hand the role of religious leaders is very large in the process of interfaith dialogue, cultural elements, customs that are humanistic in nature strengthen the process of interfaith interaction in Flores, NTT.